ANALISIS FAKTOR â FAKTOR YANG MEMPENGARUHI PERILAKU PELANGGAN BELANJA ONLINE - Maria Josephine Tyra,; Lina .; Catharina Clara (Jurnal Manajemen., 2014)
This study examines factors which is affecting online shopping customer behavior. Based on Javadi et.al. (2012), there are two model analysis in this research. First, measure affect of financial risk, product risk, incovenience risk, non-delivery risk, return policy, service and infrastructural on online shopping attitude. Second, to measure affect of domain specific innovativeness, attitude, subjective norms, and perceived behavioral control on online shopping behavior. Sample selected from customers of five online shops in Palembang surveyed was selected by snowball sampling. Analysis using multiple linier regression. The results on first model analysis showed that almost of all risks negatively affect online shopping attitude. Only incovenience risk which have positive affect. Return policy and service and infrastructural positively affect online shopping behavior. On second model, analysis shows that all independent variables positively affect on online shopping behavior. This research support empirical research about subjective norms and attitude positively support behavior. In the other side, based on the result, affect of domain specific innovativeness and perceived behavior control need a more concern on future research.